2012
DOI: 10.1002/mus.23306
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis in giant axonal neuropathy: New insights into disease mechanisms

Abstract: Several of the dysregulated proteins play a role in cytoskeletal reorganization. Based on these findings, we speculate that disturbed cytoskeletal regulation is responsible for formation of aggregates of intermediate filaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…These results indicated that the generalized disorganization of IFs in GAN patients may not involve TBCB-mediated MT disassembly and must be regulated by a yet unidentified mechanism [106]. Recently, proteomic analysis performed in fibroblasts from four GAN patients provided new insights into disease mechanisms [124]. Although the major role of gigaxonin is reported to be degradation of cytoskeleton-associated proteins, the amount of 76 structural cytoskeletal proteins was unaltered.…”
Section: Giant Axonal Neuropathymentioning
confidence: 94%
See 1 more Smart Citation
“…These results indicated that the generalized disorganization of IFs in GAN patients may not involve TBCB-mediated MT disassembly and must be regulated by a yet unidentified mechanism [106]. Recently, proteomic analysis performed in fibroblasts from four GAN patients provided new insights into disease mechanisms [124]. Although the major role of gigaxonin is reported to be degradation of cytoskeleton-associated proteins, the amount of 76 structural cytoskeletal proteins was unaltered.…”
Section: Giant Axonal Neuropathymentioning
confidence: 94%
“…In the case of fibroblasts, disturbed cytoskeletal regulation could lead to a hyperphosphorylation state of vimentin that results in massive depolymerization of vimentin filaments and finally in collapse of the vimentin network. The unpolymerized filaments are collected in the aggresome near the nucleus where they form the typical aggregates [124].…”
Section: Giant Axonal Neuropathymentioning
confidence: 99%
“…· 150 mm length · 5 lm, 100 Å column; Phenomenex), as described by Mussche et al (2012). The buffer compositions were 20 mM HCOONH 4 , 2% ACN at pH 10 for buffer A and 20 mM HCOONH 4 , 80% ACN at pH 10 for buffer B.…”
Section: Patients Fibroblast Culturesmentioning
confidence: 99%
“…Off-line LC-MS was done as described by Mussche et al (2012). Briefly, analytical reversed phase separation of the labeled peptide mixture was performed on an Ultimate Plus Dual-gradient Capillary/Nano-LC system (Dionex-LC Packings) using a C18 column (75 lm i.d.…”
Section: Nano-lc/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation